(untitled) (American Journal of Islam and Society, 2005)
This edited collection complemented a March 2001 museum exhibit and is based upon a February 2000 Columbia University conference and a threeyear Ford Foundation-sponsored research project. It provides a general overview of the history and diversity of Arab Americans in New York City and is particularly strong in the area of the arts, featuring several chapters on literature and music, including several first-person narratives. This two-part book, which surveys both the historical and the contemporary scenes, is further enhanced by forty black-and-white photographs, including thirteen by Empire State College’s Mel Rosenthal. New York contains the third largest Arab-American community, after Dearborn (Michigan) and Los Angeles. In the first chapter, Alixa Naff explains that the community was formed around 1895, when Christian missionaries in Syria encouraged Arab Christians near Mount Lebanon to work in New York for a couple of years to make money for their families. Syrian and Lebanese immigrants initially gathered at Washington Street in Lower Manhattan and soon moved to Atlantic Avenue in the South Ferry portion of Brooklyn. From 1899-1910, 56,909 Syrian immigrants arrived in New York. In the book’s first part, two historical chapters are followed by entries on literature, music, photography, and first-person accounts. Philip Kayal points out that Arab-American is a cultural and ethnic – but not a religious – category, for most Arab Americans are Christian, not Muslim. Jonathan Friedlander reveals that the first Arab-American immigrant, Antonio Bishallany, visited from Lebanon in 1854 to gather evangelical teachings for use back home. This four-page and six-photograph entry on representations in historical archives could be expanded into a larger work ...